The Effect of Instagram Communication on Consumer’s Perception of Erigo Store - Fatimah Malinda Utami; Fatin Nurul Karisma; Shafa Adha Zhafira (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The goal of the study was to find out how Erigo consumers communicate through Instagram. In addition, the study also wanted to see how they perceived the product. The object of the study was Instagram social media users. The subject for our research was the Erigo store. The number of participants involved was 171 participants. The method we use is quantitative in the form of questionnaires that we have spread through social media. From the results obtained, the author concluded that the Erigo brand deserves to promote its products on Instagram, so the Erigo brand must be able to prove itself as a good brand in the eyes of the public. Currently, Erigo has used Instagram as a platform to promote, advertise, and market products to other users or in the current alternative, Erigo can bring their products to the Instagram store So that consumers can visit Erigo's online store to view advertised products or see other products that are advertised. might attract their customers. It can be concluded, the big impact is not only Instagram itself, but also their marketing strategy and product advertisements fall to the right consumers, thus giving them a lot of benefits and will not give a perception to consumers.